logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

If $\;(x+iy)^{\large\frac{1}{3}}= a+ib\;$ where $\;x\;,y\;,a\;,b \in R\;$ show that $\; \large\frac{x}{a} - \large\frac{y}{b} = -2 (a^{2} + b^{2})$

$(a)\;-2(a^{2}+b^{2})\qquad(b)\;2(a^{2}-b^{2})\qquad(c)\;a^{2}+b^{2}\qquad(d)\;2(b^{2}-a^{2})$

Can you answer this question?
 
 

1 Answer

0 votes
Answer : $\;-2(a^{2}+b^{2})$
Explanation :
$\;(x+iy)^{\large\frac{1}{3}}= a+ib\;$
$\;(x+iy)^{\large\frac{1}{3}}= (a+ib)^{3}\;$
$= a^{3}+(ib)^{3} + 3\;.a\;.ib\;(a+ib)$
$= a^{3} -ib^{3} +3a^{2}b i +3ab^{2}i^{2}$
$= a^{3} -ib^{3} +3a^{2}b i-3ab^{2}$
$= (a^{3}-3ab^{2})+ i (3a^{2}b -b^{3}) $
$x = (a^{3}-3ab^{2})\;$ and $\;y=(3a^{2}b -b^{3})$
$\; \large\frac{x}{a} - \large\frac{y}{b} = \large\frac{a^{3} - 3ab^{2}}{a} - \large\frac{3a^{2}b-b^{3}}{b} $
$= \large\frac{a(a^{2} - 3b^{2})}{a} - \large\frac{b(3a^{2}-b^{2})}{b} $
$= a^{2} -3b^{2} - 3a^{2} +b^{2}$
$= -2a^{2} -2b^{2} $
$=-2(a^{2}+b^{2})\;.$
answered Apr 17, 2014 by yamini.v
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...